The Nurses\' Quality of Life Based on Burnout, Perceived Social Support and Psychological Hardiness - Khadijeh Hatamipour; Fatemeh Hoveida; Flora Rahimaghaee; Nahid Babaeiamiri; Jamal Ashoori (Golestan University of Medical Sciences, 2017)
Background: Nurses are responsible for maintaining and improving the health and quality of life of patients. Therefore, it is important to assess the quality of life of nurses in order to improve it. Quality of life is affected by many variables  and among them burnout, perceived social support and psychological hardiness are the leading ones. This study aimed at predicting the quality of life of nurses based on job burnout, perceived social support and psychological hardiness. Methods: This cross-sectional study was carried out on nurses working in governmental hospitals in Tehran , 2015. Four-hundred nurses were selected by multistage cluster sampling. The instruments were burnout, perceived social support, psychological hardiness and quality of life questionnaires. The data was analyzed using Pearson correlation and multiple regression model simultaneously.  Results: The results showed that the burnout and quality of life of  the nurses had a significant and negative relationship (r=-0.39) and  the perceived social support (r =0.61) and psychological hardiness (r =0.45) had a positive and significant correlation with quality of life of nurses (P<0.01). In a predictive model of burnout, perceived social support and psychological hardiness could predict 59.3 percent of the changes in quality of life (R2=0.593). Conclusion: According to the results, it is suggested that nursing executives, counselors, therapists and policy makers pay attention to the signs and the effects of  these variables , and conduct some  appropriate  programs for improving the quality of life of nurses.